2014
DOI: 10.1159/000360359
|View full text |Cite
|
Sign up to set email alerts
|

Extraoral Plasmablastic Lymphoma Detected Using Ascitic Fluid Cytology and Flow Cytometry: A Case Report with a Review of the Literature

Abstract: Background: Plasmablastic lymphoma (PL) is a relatively new category of lymphoma, which has been considered to be found predominantly in the oral cavity and has a strong association with HIV. Case: We report a case of extraoral/mesenteric PL detected using cytological examination of ascitic fluid assisted by flow cytometric (FC) analysis. The cells were positive for CD38, CD138, CD10, CD45 and CD56 and negative for CD3, CD19, CD20 and CD79a, with cytoplasmic lambda light-chain restriction. We also reviewed 67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In a review by Dorwal et al on extraoral PBL, they reported 31 HIV-negative patients, among whom 11 (35%) were EBVpositive. 7 It was reported that EBV positivity in both oral and extraoral PBL patients who were HIV-negative was 54%, whereas that in HIV-positive patients was 74%. 8 Thus, it is noteworthy that all four cases of PBL primarily arising in the maxillary sinus with HIV negativity including our present case were EBV-positive.…”
Section: Pbl Has Been Listed In the 2008 World Health Organization CLmentioning
confidence: 99%
“…In a review by Dorwal et al on extraoral PBL, they reported 31 HIV-negative patients, among whom 11 (35%) were EBVpositive. 7 It was reported that EBV positivity in both oral and extraoral PBL patients who were HIV-negative was 54%, whereas that in HIV-positive patients was 74%. 8 Thus, it is noteworthy that all four cases of PBL primarily arising in the maxillary sinus with HIV negativity including our present case were EBV-positive.…”
Section: Pbl Has Been Listed In the 2008 World Health Organization CLmentioning
confidence: 99%
“…[ 3 , 5 8 ] It is observed that there is less frequent association of extraoral PBL with HIV. [ 9 , 10 ] There are several reported cases of PBL with extraoral and osseous manifestation in addition to soft tissue PBL in immuno-competent patient . [ 5 , 6 , 8 ] No case has yet been reported PBL arising exclusively from osseous tissue in an immuno-competent person.…”
Section: Introductionmentioning
confidence: 99%